Multidisciplinary Assessment and Diagnosis of Conversion Disorder in a Patient with Foreign Accent Syndrome - Harrison N. Jones; Tyler J. Story; Timothy A. Collins; Daniel DeJoy; Christopher L. Edwards (Behavioural Neurology)
Multiple reports have described patients with disordered articulation and prosody, often following acute aphasia, dysarthria, or apraxia of speech, which results in the perception by listeners of a foreign-like accent. These features led to the term foreign accent syndrome (FAS), a speech disorder with perceptual features that suggest an indistinct, non-native speaking accent. Also correctly known as psuedoforeign accent, the speech does not typically match a specific foreign accent, but is rather a constellation of speech features that result in the perception of a foreign accent by listeners. The primary etiologies of FAS are cerebrovascular accidents or traumatic brain injuries which affect cortical and subcortical regions critical to expressive speech and language production. Far fewer cases of FAS associated with psychiatric conditions have been reported. We will present the clinical history, neurological examination, neuropsychological assessment, cognitive-behavioral and biofeedback assessments, and motor speech examination of a patient with FAS without a known vascular, traumatic, or infectious precipitant. Repeated multidisciplinary examinations of this patient provided convergent evidence in support of FAS secondary to conversion disorder. We discuss these findings and their implications for evaluation and treatment of rare neurological and psychiatric conditions.